Cleidocranial Dysplasia - Chavva, Sunanda; Reddy, Nallamilli VS Sekhar; Reddy, MR Haranatha; Badam, Rajkumar (Journal of Orofacial Research, 2012)
Cleidocranial dysplasia (CCD) is a bone disorder with cranial malformations, dental abnormalities, clavicular hypoplasia or agenesis and narrow thorax which allows approximation ofshoulders in front of chest. We report a case of CCD and discuss about it.